A rare case of hypertrophic lichen planus caused by ingestion of ink - James, Varghese; Vellore, Mridula (International Journal of Research in Medical Sciences, 2021)
Lichen planus is a papulosquamous disorder that affects the skin as well as mucous membrane. It is classified into different variants according to the location and morphology. Hypertrophic lichen planus is one of the clinical variants. Here we have described a case of four-year-old boy with unusual presentation of hypertrophic lichen planus caused by chewing refill of ballpoint pen.